Inertial measurement unit calibration with magnetometer for autonomous robot in difficult global positioning system environment - Mohd. Khairulazree Sulaiman, 1991- 638488; Tajul Ariffin Musa, supervisor 274221; Fakulti Geoinformasi dan Harta Tanah 555724 (2014)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2014